Strength and power profiling of athletes: Selecting tests and how to use the information for program design. - McGuigan, M. R.; Cormack, S. J.; Gill, N. (Strength and Conditioning Journal, 2013)
Strength and power diagnosis can provide valuable insights into the different capacities of athletes. The strength and power tests chosen should be reliable and valid and take into account the requirements of the sport and what is a meaningful change in performance. The results of these tests need to be reported in a clear, meaningful, and timely manner for coaches if they are to have maximal impact on training programs. The practitioner can use this evidence-based information in conjunction with the art of coaching to maximize training program effectiveness.